Elevated anti-müllerian hormone concentrations in blood serum of dogs with oligozoospermia or azoospermia - Beate Walter; Jessica Cremer; Laura Meder; Eva-Maria Bauer; Sven Reese; Christiane Otzdorff (Domestic Animal Endocrinology, 2026)

Investigating the associations between road traffic noise exposure at home, green spaces and stress biomarkers: A cross-sectional field study - Javier Dopico; Beat Schäffer; Mark Brink; Danielle Vienneau; Martin Röösli; Tina Maria Binz; Silvia Tobias; Nicole Bauer; Jean Marc Wunderli (Urban Forestry & Urban Greening, 2026)

Prospective LCA to support the agri-food sector’s transition towards sustainability—89th LCA discussion forum conference report - Mélanie Douziech; Christian Bauer; Maria Bystricky; Vasco Diogo; Pierre Jouannais; Jens Lansche; Eléonore Loiseau; Joan Muñoz-Liesa; Anne van den Oever; Thomas Nemecek (The International Journal of Life Cycle Assessment, 2025)
Purpose The 89th Life Cycle Assessment (LCA) Discussion Forum (DF) on the use of prospective LCA (pLCA) to support sustainability transitions of the agri-food sector was held on the 4th of February 2025 in Zurich. Methods This paper summarizes the main discussion points and challenges identified during the 89th LCA DF related to pLCA in the agri-food sector. Results The presentations highlighted recent progress in inventory and impact modelling and featured case studies related to the technology- and system-wide application of pLCA to the agri-food sector. The Q&A sessions and panel discussion highlighted challenges related to pLCA in the agri-food sector and in general. These challenges relate to missing data, the complexity of pLCA and its associated uncertainties, as well as ensuring the usefulness of the conducted evaluations. Possible solutions relate to streamlining the communication of results, adapting them to the needs of different stakeholder groups, or exploring scenarios to showcase a range of possible futures. Additionally, more frequent collaboration with other research fields could help reduce uncertainty and improve data availability. Conclusions While the challenges faced in the pLCA of agri-food systems are similar to those in other sectors, the lack of data on future developments and uncertainties is more pronounced. This is largely due to the dynamic character of these systems and their sensitivity to environmental conditions .

Enterolactone and enterodiol produced by fermentation of Valerian root extract with human fecal samples - Maria-Eleni Grafakou; Eva-Maria Pferschy-Wenzig; Olaf Kelber; Rudolf Bauer (Phytochemistry Letters, 2025)

Application of feature based molecular network analysis for the investigation of the Covid-19 remedy Hanshiyi - Stefanie Tiefenbacher; Eva-Maria Pferschy-Wenzig; Yanyan Zhou; Min Li; Xiaolin Tong; Rudolf Bauer (Phytochemistry Letters, 2025)

Toxicological problems of tattoo removal: characterization of femtosecond laser-induced fragments of Pigment Green 7 and Green Concentrate tattoo ink - Elvira Maria Bauer; Cosimo Ricci; Daniele Cecchetti; Giorgia Ciufolini; Daniel Oscar Cicero; Marco Rossi; Ettore Guerriero; Stefano Orlando; Marilena Carbone (Archives of Toxicology, 2025)
Femtosecond lasers represent a novel tool for tattoo removal as sources that can be operated at high power, potentially leading to different removal pathways and products. Consequently, the potential toxicity of its application also needs to be evaluated. In this framework, we present a comparative study of Ti:Sapphire femtosecond laser irradiation, as a function of laser power and exposure time, on water dispersions of Pigment Green 7 (PG7) and the green tattoo ink Green Concentrate (GC), which contains PG7 as its coloring agent. The treated samples were subsequently analyzed via UV‒Vis spectroscopy, gas chromatography‒mass spectrometry (GC‒MS), SEM imaging and associated statistical analysis. We found that, on average, the discoloration efficacy of femtosecond laser treatment was comparable to that of nanosecond lasers as were the decomposition products. In fact, two primary types of fragments are produced, both of which are potentially harmful, resulting either from the decomposition of chlorinated phthalocyanine (i.e., PG7) or from the active chlorination of naphthalene impurities. However, the outcomes for the PG7 and GC treatments differed significantly from each other from several points of view. The spectral intensity patterns of GC and PG7 were distinct, depending on the treatment conditions, and showed linearity with power only in the case of GC. Additionally, the relative ratios of the fragment products differed significantly, with the production rate showing a linear dependence on power only in the case of GC and no discernible trend for PG7. Shape and size distribution of the generated particles were highly dependent on the type of sample. Femtosecond laser irradiation of GCs primarily produces nanoparticles with a homogeneous size distribution, which are typically considered nontoxic. Large aggregates also formed, exhibiting a regular shape. In contrast, PG7 yielded rods and needles with aspect ratios similar to those of toxic fibers.

Knockdown resistance in Stomoxys calcitrans stable fly populations on German dairy farms: kdr alleles explain susceptibility of individual flies to deltamethrin - Ricarda Daher; Jürgen Krücken; Burkhard Bauer; Virginia Maria Góes da Silva; Sophia Reissert; Wiebke Weiher; Ard M. Nijhof; Peter-Henning Clausen; Stephan Steuber (Journal of Pest Science, 2025)
The stable fly, Stomoxys calcitrans, is a globally important pest causing stress, economic losses and transmission of pathogens in livestock. Control on commercial farms relies predominantly on the use of insecticides, with pyrethroids being the most frequently used class of insecticides in industrialised countries. Here, laboratory isolates were obtained from four dairy farms in Brandenburg (Germany) and tested for phenotypic resistance to deltamethrin in comparison to a susceptible reference isolate using topical application. Individual flies were subsequently genotyped using allele-specific real-time PCRs. Phenotypic resistance was observed in all four field isolates with resistance ratios between 46 and 119 compared to the susceptible laboratory strain. At position 1014 of the voltage-sensitive sodium channel, allele-specific PCRs detected the wild-type , kdr-his and kdr genotypes encoding leucine, histidine and phenylalanine, respectively. In the susceptible laboratory isolate, only the wild-type was identified. On the farms with very high LD 50 values, the kdr variant was most prevalent and logistic regression analysis revealed that the kdr variant increased the odds to survive exposure to deltamethrin more than the kdr-his genotype. Flies carrying two resistance alleles were less susceptible than flies that also carried one wild-type allele. In three out of four field isolates, the allele frequencies were significantly different from the expectations of the Hardy–Weinberg equilibrium suggesting ongoing selection. The data show that the phenotype can be largely explained by the kdr genotype and represent high frequencies of the L1014F kdr and L1014H kdr-his variants conferring high levels of resistance in northern Germany.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A source-to-sink perspective of an anthropogenic marker: A first assessment of microplastics concentration, pathways, and accumulation across the environment - Sébastien Rohais; John J. Armitage; Maria-Fernanda Romero-Sarmiento; Jean-Lou Pierson; Vanessa Teles; Daniela Bauer; Cyril Cassar; David Sebag; Marie-Hélène Klopffer; Maxime Pelerin (Earth-Science Reviews, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Structures and bioactivities of monomeric and dimeric carvotacetones from Sphaeranthus africanus - Huyen Thi Tran; Teresa Pirker; Eva-Maria Pferschy-Wenzig; Olaf Kunert; Loi Huynh; Rudolf Bauer (Phytochemistry, 2024)

Factors Influencing Health-Related Quality of Life of Patients with Spinocerebellar Ataxia - Niklas Weber; Maresa Buchholz; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Thomas Klockgether; Wolfgang Hoffmann; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2024)
Background Little is known about the progression of health-related quality of life (HRQoL) and predicting factors in spinocerebellar ataxia (SCA). Such knowledge is crucial to identify modifiable factors promoting everyday life with SCA and attenuating HRQoL decline. Objectives This study is to assess HRQoL progression and identify factors affecting SCA patients’ HRQoL. Methods Longitudinal data (three-year follow-up) of 310 SCA patients of the European SCA3/Machado-Joseph-Disease Initiative (ESMI) (2016-2022) and 525 SCA patients (SCA1, SCA2, SCA3 or SCA6) of the EUROSCA natural history study cohort (2006–2015) were assessed. Both large cohort studies share standardized assessments of clinical measures, SARA, INAS, PHQ-9, and HRQoL (EQ-5D-3L). The association between HRQoL and clinical measures was assessed by Spearman Correlation (r s ). Multivariable panel regression models were performed to evaluate the impact of patients’ socio-demographics, age of onset, SCA type and body mass index (BMI), and clinical measures on HRQoL progression. Results HRQoL significantly decreased over one (− 0.014, p = 0.095), two (− 0.028, p = 0.003), and three years (− 0.032, p = 0.002). Ataxia severity and mental health strongly correlated with HRQoL (r s SARA = − 0.589; r s PHQ-9 = − 0.507). HRQoL more intensively declined in male (ß = − 0.024, p = 0.038) patients with an earlier age of onset (ß = 0.002, p = 0.058). Higher progression of ataxia severity (ß = − 0.010, p ≤ 0.001), mental health problems (ß = − 0.012, p < 0.001), and higher BMI (ß = − 0.003, p = 0.029) caused more severe decline of patients’ HRQoL over time. Discussion In absence of curative treatments, stronger focus on mental health and weight influence could help clinical evaluation and accompany treatment improving SCA patients’ HRQoL, especially in male patients with early disease onset.

Efficiency of the bank filtration for removing organic priority substances and contaminants of emerging concern: A critical review - Attila Csaba Kondor; Anna Viktória Vancsik; László Bauer; Lili Szabó; Zoltán Szalai; Gergely Jakab; Gábor Maász; Marta Pedrosa; Maria José Sampaio; Ana Rita Lado Ribeiro (Environmental Pollution, 2024)

Characterization of metabolites from milk thistle flavonolignans generated by human fecal microbiota - Eva-Maria Pferschy-Wenzig; Olaf Kunert; Timo Thumann; Christine Moissl-Eichinger; Rudolf Bauer (Phytochemistry, 2023)

PAR regulation of photoprotection in Phaeodactylum tricornutum (Bacillariophyceae): Roles of doses and irradiances - Herculano Cella; Camila Nader; Camila Lisarb Velasquez Bastolla; José Bonomi-Barufi; Carlos Yure B. Oliveira; Rafael Garcia Lopes; Jacó Joaquim Mattos; Cláudia Marlene Bauer; Marcelo Maraschin; Leonardo Rubi Rörig; Afonso Celso Dias Bainy; Maria Risoleta Freire Marques; et al. (Journal of Applied Phycology, 2023)

Health-Related Quality of Life in Patients with Spinocerebellar Ataxia: a Validation Study of the EQ-5D-3L - Maresa Buchholz; Niklas Weber; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Feng Xie; Thomas Klockgether; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2023)
Although health-related quality of life (HRQoL) has developed into a crucial outcome parameter in clinical research, evidence of the EQ-5D-3L validation performance is lacking in patients with spinocerebellar ataxia (SCA) types 1, 2, 3, and 6. The objective of this study is to assess the acceptability, validity, reliability, and responsiveness of the EQ-5D-3L. For n = 842 predominantly European SCA patients of two longitudinal cohort studies, the EQ-5D-3L, PHQ-9 (Patient Health Questionnaire), and ataxia-specific clinical assessments (SARA: Scale for Assessment and Rating of Ataxia; ADL: activities of daily living as part of Friedreich’s Ataxia Rating Scale; INAS: Inventory of Non-Ataxia Signs) were assessed at baseline and multiple annual follow-ups. The EQ-5D-3L was evaluated regarding acceptability, distribution properties, convergent and known-groups validity, test-retest reliability, and effect size measures to analyze health changes. The non-item response was low (EQ-5D-3L index: 0.8%; EQ-VAS: 3.4%). Ceiling effects occurred in 9.9% (EQ-5D-3L) and 3.0% (EQ-VAS) with a mean EQ-5D-3L index of 0.65 ± 0.21. In total, convergent validity showed moderate to strong Spearman’s rho ( r s > 0.3) coefficients comparing EQ-5D-3L and EQ-VAS with PHQ-9, SARA, ADL, and INAS. EQ-5D-3L could discriminate between groups of age, SARA, ADL, and INAS. Intra-class correlation coefficients (EQ-5D-3L ICC : 0.95/EQ-VAS ICC : 0.88) and Kappa statistics (range 0.44 to 0.93 for EQ-5D-3L items) indicated tolerable reliability. EQ-5D-3L shows small (effect size < 0.3) to moderate (effect size 0.3–0.59) health changes regarding ataxia severity. The analysis confirms an acceptable, reliable, valid, and responsive recommended EQ-5D-3L in SCA patients, measuring the HRQoL adequately, besides well-established clinical instruments.

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Influence of Cell Wall on Biomolecules Biosynthesis in Chlamydomonas reinhardtii Strains Exposed to Magnetic Fields - Lenon M. Bauer; Maria da Gloria Esquível; Jorge Alberto V. Costa; Ana Priscila C. da Rosa; Lucielen O. Santos (Current Microbiology, 2023)

Integrating Indigenous Traditional Ecological Knowledge of land into land management through Indigenous-academic partnerships - Heather Sauyaq Jean Gordon (Iñupiaq); J. Ashleigh Ross; Cheryl Bauer-Armstrong; Maria Moreno; Rachel Byington (Choctaw); Nicole Bowman (Lunaape/Mohican) (Land Use Policy, 2023)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Laser vs. thermal treatments of green pigment PG36: coincidence and toxicity of processes - Elvira Maria Bauer; Daniele Cecchetti; Ettore Guerriero; Steven Nisticò; Giulia Germinario; Simona Sennato; Lorenzo Gontrani; Pietro Tagliatesta; Marilena Carbone (Archives of Toxicology, 2021)
Comparative laser and thermal treatments were carried out on PG36, a green phthalocyanine-based pigment, permitted in European countries where legislation on tattoo composition was issued. Prior to the treatments, PG36 was characterized by SEM imaging, EDX, IR and UV–Vis spectroscopies, revealing an excess of Si and C and O as compared to the pure halogenated Cu-phthalocyanine. Laser treatments were carried out with a Nd:YAG device applied to H 2 O and propan-2-ol dispersions. Pyrolysis and calcinations were carried out in air or under N 2 flow. The outcome of the different procedures was analyzed by UV–Vis spectroscopy, GC–mass spectrometry, X-ray diffraction of the solid residues, SEM microscopy and dynamic light scattering. The comparative analysis indicated the production of different fragment compounds depending on the treatment, (pyrolysis or laser), and, to some extent, to the solvent of the dispersion, with pyrolysis generating a larger number of hazardous compounds. Hydrocarbons and cyclic siloxanes present as additives in PG36 were stable or degraded depending on the treatment. The morphology of the products is also treatment-dependent with nanoparticles

Environmental and biotic variables in carp (Cyprinus carpio) ponds: organic vs. conventional management - Maria Anton-Pardo; David Hlaváč; Christian Bauer; Zdeněk Adámek (Aquaculture International, 2020)

Treatments of a phthalocyanine-based green ink for tattoo removal purposes: generation of toxic fragments and potentially harmful morphologies - Elvira Maria Bauer; Emanuele Vincenzo Scibetta; Daniele Cecchetti; Susanna Piccirillo; Simonetta Antonaroli; Simona Sennato; Marina Cerasa; Pietro Tagliatesta; Marilena Carbone (Archives of Toxicology, 2020)

The global biogeography of lizard functional groups - Enav Vidan; Maria Novosolov; Aaron M. Bauer; Fernando Castro Herrera; Laurent Chirio; Cristiano de Campos Nogueira; Tiffany M. Doan; Amir Lewin; Danny Meirte; Zoltan T. Nagy; Daniel Pincheira‐Donoso; Oliver J.S. Tallowin; et al. (Journal of Biogeography, 2019)
Aim Understanding the mechanisms determining species richness is a primary goal of biogeography. Richness patterns of sub‐groups within a taxon are usually assumed to be driven by similar processes. However, if richness of distinct ecological strategies respond differently to the same processes, inferences made for an entire taxon may be misleading. We deconstruct the global lizard assemblage into functional groups and examine the congruence among richness patterns between them. We further examine the species richness – functional richness relationship to elucidate the way functional diversity contributes to the overall species richness patterns. Location Global. Methods Using comprehensive biological trait databases we classified the global lizard assemblage into ecological strategies based on body size, diet, activity times and microhabitat preferences, using Archetypal Analysis. We then examined spatial gradients in the richness of each strategy at the one‐degree grid cell, biome, and realm scales. Results We found that lizards can best be characterized by seven “ecological strategies”: scansorial , terrestrial , nocturnal , herbivorous , fossorial , large, and semi‐aquatic . There are large differences among the global richness patterns of these strategies. While the major richness hotspot for lizards in general is in Australia, several strategies exhibit highest richness in the Amazon Basin. Importantly, the global maximum in lizard species richness is achieved at intermediate values of functional diversity and increasing functional diversity further result in a slow decline of species richness. Main conclusions The deconstruction of the global lizard assemblage along multiple ecological axes offers a new way to conceive lizard diversity patterns. It suggests that local lizard richness mostly increases when species belonging to particular ecological strategies become hyper‐diverse there, and not because more ecological types are present in the most species rich localities. Thus maximum richness and maximum ecological diversity do not overlap. These results shed light on the global richness pattern of lizards, and highlight previously unidentified spatial patterns in understudied functional groups.

Integrative Taxonomy of Meloidogyne oryzae (Nematoda: Meloidogyninae) parasitizing rice crops in Southern Brazil - Vanessa Silva da Mattos; Juvenil Enrique Cares; Cesar Bauer Gomes; Ana Cristina Meneses Mendes Gomes; Jessica da Mata dos Santos Monteiro; Guillermo Marcello Gomez; Philippe Castagnone-Sereno; Regina Maria Dechechi Gomes Carneiro (European Journal of Plant Pathology, 2018)

Non-economic losses from climate change: opportunities for policy-oriented research - Olivia Maria Serdeczny; Steffen Bauer; Saleemul Huq (Climate and Development, 2018)

The Eurasian hot nightlife: Environmental forces associated with nocturnality in lizards - Enav Vidan; Uri Roll; Aaron Bauer; Lee Grismer; Peng Guo; Erez Maza; Maria Novosolov; Roberto Sindaco; Philipp Wagner; Jonathan Belmaker; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim Lizards are ancestrally diurnal, and most of them remain so. Nocturnality is common among lizards, but the environmental factors associated with lizard nocturnal activity are still unknown. Here, we contrasted the ambient temperature and productivity hypotheses, where we predicted that cold temperatures will pose a stonger limit to nocturnal species richness than diurnal lizards. Moreover, we contrasted the relative importance of annual, day and night mean temperatures to pinpoint the drivers of nocturnal lizard richness. Location Mainland Eurasia. Methods We collected distribution range and activity time data for all 1,113 lizard species found throughout mainland Eurasia. This represents the largest geographical scope to date, for studies of lizard species richness. We examined the spatial patterns of nocturnal species richness in relationship to diurnal species richness across environmental gradients of ambient temperature and productivity. Results Nocturnal lizards are richest in the tropics and in deserts, and their richness decreases with latitude. However, nocturnal lizards are absent from the highest latitudes and coldest regions inhabited by lizards. Diurnal and nocturnal lizards respond in a similar manner to climatic factors. Ambient temperature has a strong influence on both, whereas productivity is more tightly related to the proportion of nocturnal species. Main conclusions Nocturnality is widespread among Eurasian lizards. However, nocturnal lizards are absent from invariably cold regions, and low temperatures seem to be a limiting factor for lizard activity period. We suggest that the year‐round warm nights of the tropics reduce the cost of being active at night and open the nocturnal niche for many lizards. In hot deserts, the combination of hot days and aridity increases the cost of diurnal activity, whereas nocturnal activity provides a shelter from these extreme conditions.

Localization and pneumococcal alteration of junction proteins in the human alveolar–capillary compartment - Andrea Peter; Diana Fatykhova; Olivia Kershaw; Achim D. Gruber; Jens Rueckert; Jens Neudecker; Mario Toennies; Torsten T. Bauer; Paul Schneider; Maria Schimek; Stephan Eggeling; Norbert Suttorp; et al. (Histochemistry and Cell Biology, 2017)

An extracellular proteasome releases endostatin from human collagen XVIII - Maria L. V. Reiss-Pistilli; Detlef Schuppan; Madalena M. S. Barroso; Iranaia Assunção-Miranda; Shirley Farias; Letícia Lery; Michael Bauer; Luiz Juliano; Maria A. Juliano; Tatiana Coelho-Sampaio (Angiogenesis, 2017)

Patterns of species richness, endemism and environmental gradients of African reptiles - Amir Lewin; Anat Feldman; Aaron M. Bauer; Jonathan Belmaker; Donald G. Broadley; Laurent Chirio; Yuval Itescu; Matthew LeBreton; Erez Maza; Danny Meirte; Zoltán T. Nagy; Maria Novosolov; et al. (Journal of Biogeography, 2016)
Aim To map and assess the richness patterns of reptiles (and included groups: amphisbaenians, crocodiles, lizards, snakes and turtles) in Africa, quantify the overlap in species richness of reptiles (and included groups) with the other terrestrial vertebrate classes, investigate the environmental correlates underlying these patterns, and evaluate the role of range size on richness patterns. Location Africa. Methods We assembled a data set of distributions of all African reptile species. We tested the spatial congruence of reptile richness with that of amphibians, birds and mammals. We further tested the relative importance of temperature, precipitation, elevation range and net primary productivity for species richness over two spatial scales (ecoregions and 1° grids). We arranged reptile and vertebrate groups into range‐size quartiles in order to evaluate the role of range size in producing richness patterns. Results Reptile, amphibian, bird and mammal richness are largely congruent ( r = 0.79–0.86) and respond similarly to environmental variables (mainly productivity and precipitation). Ecoregion size accounts for more variation in the richness of reptiles than in that of other groups. Lizard distributions are distinct with several areas of high species richness where other vertebrate groups (including snakes) are species‐poor, especially in arid ecoregions. Habitat heterogeneity is the best predictor of narrow‐ranging species, but remains relatively important in explaining lizard richness even for species with large range sizes. Main conclusions Reptile richness varies with similar environmental variables as the other vertebrates in Africa, reflecting the disproportionate influence of snakes on reptile richness, a result of their large ranges. Richness gradients of narrow‐ranged vertebrates differ from those of widespread taxa, which may demonstrate different centres of endemism for reptile subclades in Africa. Lizard richness varies mostly with habitat heterogeneity independent of range size, which suggests that the difference in response of lizards is due to their ecological characteristics. These results, over two spatial scales and multiple range‐size quartiles, allow us to reliably interpret the influence of environmental variables on patterns of reptile richness and congruency.

The Mystery of Antibodies Against Polyethylene Glycol (PEG) - What do we Know? - Christian Lubich; Peter Allacher; Maurus de la Rosa; Alexander Bauer; Thomas Prenninger; Frank Michael Horling; Jürgen Siekmann; Johannes Oldenburg; Friedrich Scheiflinger; Birgit Maria Reipert (Pharmaceutical Research, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

The Carbon Footprint of Games Distribution - Kieren Mayers; Jonathan Koomey; Rebecca Hall; Maria Bauer; Chris France; Amanda Webb (Journal of Industrial Ecology, 2015)
Summary This research investigates the carbon footprint of the lifecycle of console games, using the example of PlayStation®3 distribution in the UK. We estimate total carbon equivalent emissions for an average 8.8‐gigabyte (GB) game based on data for 2010. The bulk of emissions are accounted for by game play, followed by production and distribution. Two delivery scenarios are compared: The first examines Blu‐ray discs (BDs) delivered by retail stores, and the second, games files downloaded over broadband Internet. Contrary to findings in previous research on music distribution, distribution of games by physical BDs results in lower greenhouse gas emissions than by Internet download. The estimated carbon emissions from downloading only fall definitively below that of BDs for games smaller than 1.3 GB. Sensitivity analysis indicates that as average game file sizes increase, and the energy intensity of the Internet falls, the file size at which BDs would result in lower emissions than downloads could shift either up‐ or downward over the next few years. Overall, the results appear to be broadly applicable to title games within the European Union (EU), and for larger‐than‐average sized games in the United States. Further research would be needed to confirm whether similar findings would apply in future years with changes in game size and Internet efficiency. The study findings serve to illustrate why it is not always true that digital distribution of media will have lower carbon emissions than distribution by physical means when file sizes are large.

Late bloomers and baby boomers: ecological drivers of longevity in squamates and the tuatara - Inon Scharf; Anat Feldman; Maria Novosolov; Daniel Pincheira‐Donoso; Indraneil Das; Monika Böhm; Peter Uetz; Omar Torres‐Carvajal; Aaron Bauer; Uri Roll; Shai Meiri (Global Ecology and Biogeography, 2015)
Aim Longevity is an important life‐history trait, directly linked to the core attributes of fitness (reproduction and survival), yet large‐scale comparative studies quantifying its implications for the ecology and life history of ectotherms are scarce. We tested the allometry of longevity in squamates and the tuatara, and determined how longevity is related to key environmental characteristics and life‐history traits. Predictions based on life‐history theory are expected to hold true for ectotherms, similarly to mammals and birds. Location World‐wide. Methods We assembled from the literature a dataset of the maximum longevities of more than a thousand squamate species, representing c . 10% of their known species diversity, their phylogenetic relationships and multiple life‐history and ecological variables. Correcting for phylogeny, we modelled the link between squamate longevity and both key life‐history traits, such as body mass and age at first reproduction, and important environmental factors, such as latitude and primary productivity within species distributional ranges. Results Large‐bodied species live for longer than small ones, but body size explains far less of the variance in longevity than it does in mammals and birds. Accounting for body size, squamate brood frequency is negatively correlated with longevity, while age at first reproduction is positively correlated with longevity. This points to a continuum of slow‐to‐fast life‐history strategies. Squamates in high latitudes and cold regions live for longer, probably because a shorter season of activity translates to slower development, older age at first reproduction and hence to increased longevity. Individuals live longer in captivity than in the wild. Herbivorous and omnivorous squamates live for longer than carnivorous ones. We postulate that low‐quality nutrition reduces growth rates, promotes a relative decline in reproductive rates and thus prolongs life. Main conclusions Our results support key predictions from life‐history theory and suggest that reproducing more slowly and at older ages, being herbivorous and, plausibly, lowering metabolism, result in increased longevity.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Are lizards feeling the heat? A tale of ecology and evolution under two temperatures - Shai Meiri; Aaron M. Bauer; Laurent Chirio; Guarino R. Colli; Indraneil Das; Tiffany M. Doan; Anat Feldman; Fernando‐Castro Herrera; Maria Novosolov; Panayiotis Pafilis; Daniel Pincheira‐Donoso; Gary Powney; et al. (Global Ecology and Biogeography, 2013)
Aim Temperature influences most components of animal ecology and life history – but what kind of temperature? Physiologists usually examine the influence of body temperatures, while biogeographers and macroecologists tend to focus on environmental temperatures. We aim to examine the relationship between these two measures, to determine the factors that affect lizard body temperatures and to test the effect of both temperature measures on lizard life history. Location World‐wide. Methods We used a large (861 species) global dataset of lizard body temperatures, and the mean annual temperatures across their geographic ranges to examine the relationships between body and mean annual temperatures. We then examined factors influencing body temperatures, and tested for the influence of both on ecological and life‐history traits while accounting for the influence of shared ancestry. Results Body temperatures and mean annual temperatures are uncorrelated. However, accounting for activity time (nocturnal species have low body temperatures), use of space (fossorial and semi‐aquatic species are ‘colder’), insularity (mainland species are ‘hotter’) and phylogeny, the two temperatures are positively correlated. High body temperatures are only associated with larger hatchlings and increased rates of biomass production. Annual temperatures are positively correlated with clutch frequency and annual longevity, and negatively correlated with clutch size, age at first reproduction and longevity. Main conclusions Lizards with low body temperatures do not seem to have ‘slower’ life‐history attributes than species with high body temperatures. The longer seasons prevalent in warm regions, and physiological processes that operate while lizards are inactive (but warm enough), make environmental temperatures better predictors of lizard life‐history variation than body temperatures. This surprisingly greater effect of environmental temperatures on lizard life histories hints that global warming may have a profound influence on lizard ecology and evolution.

Characterization of identity, metabolism and androgenic activity of 17-hydroxyandrosta-3,5-diene by GC–MS and a yeast transactivation system - Anne Bauer; Felicitas Rataj; Oliver Zierau; Patricia Anielski; Joachim Große; Maria-Kristina Parr; Günter Vollmer; Detlef Thieme (Archives of Toxicology, 2012)

Spinocerebellar Ataxia Types 1, 2, 3 and 6: the Clinical Spectrum of Ataxia and Morphometric Brainstem and Cerebellar Findings - Heike Jacobi; Till-Karsten Hauser; Paola Giunti; Christoph Globas; Peter Bauer; Tanja Schmitz-Hübsch; László Baliko; Alessandro Filla; Caterina Mariotti; Maria Rakowicz; Perine Charles; Pascale Ribai; et al. (The Cerebellum, 2012)

Indoor and outdoor atmospheric fungal spores in the São Paulo metropolitan area (Brazil): species and numeric concentrations - Fábio Luiz Teixeira Gonçalves; Heidi Bauer; Maria Regina Alves Cardoso; Sandra Pukinskas; Dulcilena Matos; Márcia Melhem; Hans Puxbaum (International Journal of Biometeorology, 2010)

Sialic acid metabolism is involved in the regulation of gene expression during neuronal differentiation of PC12 cells - Maria Kontou; Christian Bauer; Werner Reutter; Rüdiger Horstkorte (Glycoconjugate Journal, 2008)

Hydrocarbons Emissions from a Municipal Wastewater Treatment Pilot Plant in Vienna - Usha Sree; Heidi Bauer; Maria Fuerhacker; Reinhard Ellinger; Heidrun Schmidt; Hans Puxbaum (Water, Air, & Soil Pollution, 2000)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)